Pendampingan Pada Remaja Dalam Menurunkan Nyeri Dismenorea Dengan Pijat Endorphine Di Kabupaten Bulukumba - Jusni; Rahmaniyah. R; Arfiani; Ni Luh Gede Sri Wahyudianti (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
Adolescence is a transition period from childhood to adulthood, experiencing physical, hormonal and sexual changes. One of the changes that occurs is menstruation. Menstruation or menstruation is a physiological change that occurs in accordance with a woman's body cycle and is influenced by reproductive hormones. Menstruation can cause discomfort, one of which is dysmenorrhea. Dysmenorrhea refers to pain, soreness and cramps felt in the lower abdomen to the back which can interfere with daily activities. The incidence of dysmenorrhoea in Indonesia reached 54.98%. Dysmenorrhea pain can be treated, one way, with non-pharmacological measures, namely endorphine massage. This massage functions to stimulate the body to release endorphin compounds which are pain relievers and can create a feeling of comfort. The aim of this mentoring service is to reduce dysmenorrhoea pain in students. Demonstration and intervention methods, the target of this activity is all 10 students of the Tahirah Al Baeti Bulukumba Midwifery Academy who experience dysmenorrhoea. Results: there was a reduction in dysmenorrhea pain in students at the Tahirah Al Baeti Bulukumba Midwifery Academy after endorphine massage, so it can be concluded that assisting teenagers with endorphine massage can be used as an effort to reduce dysmenorrhoea pain.